ELECTRONIC WORD OF MOUTH DAN PURCHASE INTENTION: PERAN MEDIASI BRAND IMAGE - Inahasari, Endah Dwi; Handayani, Wahyu Prabawati Putri (Universitas Muhammadiyah Palembang, 2024)
ABSTRACT Purpose– Testing and analyzing the significance of the positive influence of electronic word of mouth on purchase intention, electronic word of mouth on brand image, and brand image on purchase intention is the aim of this study. Besides that, the mediating role of brand image between electronic word of mouth on purchase intention was also tested in this study.Design/methodology– The sample used is 100 respondents from Instagram followers @99outfitstore. Path analysis with linear regression equations is used as a data analysis technique. Findings - The results show that the variable electronic word of mouth have a significant positive effect on brand image. Variable brand image have a significant positive effect on purchase intention. In addition, brand image has a mediating effect between electronic word of mouth and purchase intention for Ninetynine fashion products